Sensitivity to reward and adolescents’ unhealthy snacking and drinking behavior: The role of hedonic eating styles and availability - De Cock, Nathalie; Van Lippevelde, Wendy; Goossens, Lien; De Clercq, Bart; Vangeel, Jolien; Lachat, Carl; Beullens, Kathleen; Huybregts, Lieven; Vervoort, Leentje; Eggermont, Steven; Maes, Lea; Braet, Caroline; et al. (Springer, 2016)
Although previous research found a positive association between sensitivity to reward (SR) and adolescents' unhealthy snacking and drinking behavior, mechanisms explaining these associations remain to be explored. The present study will therefore examine whether the associations between SR and unhealthy snack and/or sugar-sweetened beverage (SSB) intake are mediated by external and/or emotional eating and if this mediation is moderated by availability at home or at school.Cross-sectional data on snacking, availability of snacks at home and at school, SR (BAS drive scale) and external and emotional eating (Dutch eating behavior questionnaire) of Flemish adolescents (n = 1104, mean age = 14.7 ± 0.8 years; 51 % boys; 18.0% overweight) in 20 schools spread across Flanders were collected. Moderated mediation analyses were conducted using generalized structural equation modeling in three steps: (1) direct association between SR and unhealthy snack or SSB intake, (2) mediation of either external or emotional eating and (3) interaction of home or school availability and emotional or external eating.Partial mediation of external eating (a*b = 0.69, p < 0.05) and of emotional eating (a*b = 0.92, p < 0.01) in the relation between SR and intake of unhealthy snacks was found (step 2). The relation between SR and SSB intake was not mediated by external or emotional eating (step 2). No moderation effects of home or school availability were found (step 3).Our findings indicate that the association between SR and the consumption of unhealthy snacks is partially explained by external and emotional eating in a population-based sample of adolescents irrespective of the home or school availability of these foods.